2019
DOI: 10.1136/bmjopen-2018-027058
|View full text |Cite
|
Sign up to set email alerts
|

Stress management in obesity during a thermal spa residential programme (ObesiStress): protocol for a randomised controlled trial study

Abstract: IntroductionStress and obesity are two public health issues. The relationship between obesity and stress is biological through the actions of stress on the major hormones that regulate appetite (leptin and ghrelin). Many spa resorts in France specialise in the treatment of obesity, but no thermal spa currently proposes a specific programme to manage stress in obesity. The ObesiStress protocol has been designed to offer a new residential stress management programme. This thermal spa treatment of obesity impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
0
10
0
Order By: Relevance
“…Regression analysis revealed that the risk of NWO was lower in females with a higher score in stress management behavior, which was consistent with the previous researches that stress had been shown as a key risk factor affecting obesity, 42 and psychological stress in the family led to childhood obesity. 43 Stress can lead to obesity through inappropriate eating behavior, 44 while relaxation can reduce emotional eating and improve cognitive restraint, thereby reducing weight. 45 In addition, people who are stressed are also the most difficult to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…Regression analysis revealed that the risk of NWO was lower in females with a higher score in stress management behavior, which was consistent with the previous researches that stress had been shown as a key risk factor affecting obesity, 42 and psychological stress in the family led to childhood obesity. 43 Stress can lead to obesity through inappropriate eating behavior, 44 while relaxation can reduce emotional eating and improve cognitive restraint, thereby reducing weight. 45 In addition, people who are stressed are also the most difficult to lose weight.…”
Section: Discussionmentioning
confidence: 99%
“…In practical terms, an increase of the LF component is generally considered to be a consequence of an increased sympathetic activity [38]. HF power represents the most efferent vagal (parasympathetic) activity to the sinus node [8,[39][40][41][42]. Therefore, an increase of the HF component reflects an increased parasympathetic activity.…”
Section: Data Extractionmentioning
confidence: 99%
“…To our knowledge, no meta-analysis to date has examined the effects of acute stress on ghrelin levels. Moreover, stress and obesity are intrinsically linked [9]. Stress has been suggested to lead to obesity via inappropriate eating behaviors [10].…”
Section: Introductionmentioning
confidence: 99%